Efektivitas Kuota Gender dalam Sistem Pencalonan Pemilu terhadap Keterwakilan Perempuan di DPR RI - Vallerian Antaresa; Muhammad Fahreza Ramadan; Muhammad Putra Tyanto; Aniqotul Ummah; Chomariyana Kartika Hesti (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Gender quota policies constitute an important affirmative action mechanism for promoting women’s political representation in democratic institutions. This study investigates the effectiveness of gender quotas in Indonesia’s electoral nomination system and examines the political and social factors shaping their implementation in the House of Representatives (DPR RI). Employing a descriptive qualitative approach, the analysis is grounded in theories of political representation and gender quotas. The findings indicate that quota regulations have contributed to a significant increase in the number of women candidates and improved women’s descriptive representation in parliament. Nevertheless, greater numerical representation has not been consistently translated into stronger substantive influence over legislative decision-making and policy outcomes. The effectiveness of quota implementation remains constrained by internal political party recruitment processes, the dynamics of the open-list proportional electoral system, unequal access to political resources, and the persistence of patriarchal norms that limit women’s participation in politics. These structural and cultural barriers continue to affect women’s electoral competitiveness and political influence. Strengthening women’s representation therefore requires not only quota-based regulations but also institutional reforms within political parties, improved access to political resources, and broader transformations in political culture to ensure more equitable and meaningful democratic participation.